State of play [videorecording (DVD)] - Macdonald, Kevin, 1967-; Crowe, Russell, 1964-; Affleck, Ben, 1972-; McAdams, Rachel, 1978-; Mirren, Helen; Wright, Robin, 1966-; Bateman, Jason (Universal Studios Home Entertainment, 2009)
When D.C. reporter Cal McCaffrey is assigned to investigate the murder of an assistant to an up-and-coming politician, he uncovers a conspiracy that threatens to bring down the nation's power structures. In a town of spin-doctors and wealthy power brokers, he will discover one truth: when fortunes are at stake, no one's integrity, love, or life is safe.